Guarantees of Legitimacy of State Authority - Mohammed, Iman Jassam (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Abstract Research Significance the subject is important since it investigates legitimacy and authority and discusses it according to fundamental law and jurispru-dence, where the most important negative points are highlighted, as well as justifications and theories performed by fundamental law jurists, in addition to discussing religious theories. Research Motivation: research into democrat-ic and non-democratic regimes is critical for establishing legitimacy in which the governed can have a sense of loyalty and citizenship. Since an independ-ent and effective judiciary is necessary for the realization of constitutional legitimacy and stability, it becomes crucial to high-light its vital role in ensuring the legitimacy of the state's authority, as well as the achievement of basic state guarantees and the protection. Problem Statement: The research problem arises from the ambiguity of the legitimacy concept of state authority, given the significance of the legitimacy concept in the state, as well as the reality of authority in terms of the extent to which decisions are issued by the ruler if they are appropriate and support legitimacy.